Species-specific cloned DNA probes for the identification of Campylobacter hyointestinalis. - Gebhart, C J (1989)
Conventional microbiological methods for isolating and identifying Campylobacter species are laborious, tedious, and subjective. Because of the increasing importance of Campylobacter species in human and animal diseases and the recent emergence of many new species and atypical strains, we are developing chromosomal DNA probes for rapid and simple identification of Campylobacter species, especially those of veterinary importance. We report the cloning and characterization of chromosomal DNA fragments from Campylobacter hyointestinalis, an organism isolated from pigs with proliferative enteritis. To obtain C. hyointestinalis-specific probes, chromosomal DNA fragments from C. hyointestinalis were cloned into plasmid vector pGEM-3Z. Recombinant plasmids were screened for C. hyointestinalis-specific inserts by DNA hybridization, using chromosomal DNA from either C. hyointestinalis or C. fetus which had been 32P labeled. Recombinants which hybridized to C. hyointestinalis, but not C. fetus, DNA were 32P labeled and screened further for sensitivity and specificity. Three probes were identified that were species specific and capable of detecting 10(4) C. hyointestinalis organisms by bacterial spot blotting in 48 h. We anticipate that these probes will be useful for routine species identification and for epidemiological studies.